On Psychoanalytical Formation and its Regulation in Italy - Sergio Contardi (EJP import test, 2022)
Summary: Based on some consideration into the Italian law 56/89 which regulates the training of psychotherapists, this paper tries to demonstrate – contrary to what is commonly stated – that psychoanalysis cannot be subjected to a pattern of training without perverting the nature of its own essence. At the same time the author wonders about his own experience in psychoanalytic associations today; in his opinion, the psychoanalytic societies themselves should give up the so-called psychoanalyst’s training as a core purpose. Thus they have always arbitrarily regulated what “becoming a psychoanalyst” meant and were therefore able to find a way to assimilate psychoanalysis and psychotherapy: this position caused a confusion which influences the Italian regulation of training in psychoanalysis.
Keywords: Analytic Act and Acts; Desire & amp; Truth; Exile; Psychoanalytic Associations; psychotherapy; Regulations; Training in psychoanalysis